Farmers' Decision to Adoption of Modern Irrigation Systems Under Risk Condition: Application of Stochastic Efficiency With Respect to a Function Approach - Jahangirpour, Dorna; Zibaei, Mansour (Frontiers in Water, 2022)
To effectively tackle the issue of increasing irrigation water scarcity, farmers need to convert to modern irrigation systems with lower water use while achieving higher yields and profitability. Unlike the government support to cover a proportion of irrigation modernizing costs by public subsidies in Iran, the adoption rate is low. This is due to farmers' uncertainty about the trade-off between benefits from yield improvement and the added production costs. The historical gross margin of barley, wheat, forage corn, and tomato under surface, drip, permanent sprinkler, and semi-permanent sprinkler irrigation systems was generated using simulation and survey-based data for yield and published data for costs and prices over a 5-year period (2009–2015). The stochastic dominance (SD) and stochastic efficiency with respect to a function (SERF) approaches were used to evaluate the risk efficiency of various irrigation systems for main crops in the Bakhtegan Basin. Estimating certainty equivalent (CE), we ranked irrigation alternatives at different absolute risk-aversion coefficient (ra) levels. The findings show that drip irrigation systems for forage corn and tomato have higher CE values at all levels of absolute risk-aversion coefficient; however, the preferred system for barley and wheat varies with ra. Moreover, estimated risk premiums revealed that risk-neutral farmers would pay to move from surface systems to more efficient systems, whereas risk-averse farmers need to be paid to have the tendency to change their irrigation system. The important policy implication of these results is that risk premiums can consider justifying subsidy allocation in a manner that induces farmers to more risk-efficient irrigation systems.